Rancang Bangun Aplikasi Berbasis Web Perpustakaan Fakultas Dakwah dan Komunikasi UINSU - Boby Amari, Ahmad; Faiza, Nayla (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to design and build a web-based library application at the Faculty of Da'wah and Communication, State Islamic University of North Sumatra. (UINSU). In the digital era, conventional library management faces various challenges, including difficulties in book search and member data management. Therefore, an integrated and efficient system is needed to enhance accessibility and simplify the process of borrowing and returning books. The designed application is expected to provide features such as online book search, borrowing, and real-time member data management. The research method used is Research and Development (R&D) with a Waterfall approach, which includes needs analysis, system design, implementation, and testing. The technologies used in the development of this application include the PHP programming language, MySQL database, and Laravel framework. The research results show that this application not only improves the operational efficiency of the library but also provides a better user experience. With the presence of automatic notification features for book returns and an analytical dashboard for usage monitoring, this application is expected to reduce late returns and assist management in decision-making related to the library collection. In addition, this system is designed to be integrated with the academic information system at UINSU, enabling more efficient data exchange. The development of this application is a strategic step in modernizing library services in the higher education environment, in line with the ongoing digital transformation vision. Thus, this web-based library application is expected to serve as a model for other faculties in developing similar systems, providing benefits to the academic community, and improving the overall quality of library services.